Solar Desalination by Evaporation-Condensation Process (Sebha University Conference Proceedings, 2025)
World-wide water scarcity, especially in the developing world, indicates a pressing need to develop inexpensive, decentralized small-scale desalination technologies which use renewable resources of energy. However, conventional desalination technologies are usually large-scale, technology intensive system most suitable for the energy rich and economically advanced regions of the world. They also cause environmental pollution because they are fossil fuel driven and also because of the problem of brine disposal. Solar desalination with a evaporation and condensation process has proven to be an efficient means of utilizing solar energy for the production of fresh water from saline or sea water. This study presents several advantages such as flexibility in capacity, moderate installation and operating costs, simplicity, and possibility of using low temperature energy such as geothermal and solar. In this paper, the objective is to experimentally install a solar desalination prototype applies evaporation and condensation principle with minimum low cost of fresh water production and also simplicity in terms of the technology applied. Thus, through this study and prototype installation, which will be a platform to drive the commercialization of a solar desalination based on evaporation and condensation principle due to incoming short fresh water supply in future especially for small quantities in remotes. The results of study show that a total mass transfer of a fresh water production of 0.00312 L/min. Also the average thermal efficiency of process is 34%. Moreover, the efficiency of evaporator and condenser are 37% and 6% respectively.